PROCESSING PROGRAM, PROCESSING DEVICE, AND PROCESSING METHOD - YAMAMOTO YOSHIAKI; YOSHIMURA RYUSUKE; MIYAWAKI MASARU; MIURA KASUMI (2009)
PROBLEM TO BE SOLVED: To reduce a user's workload associated with change of component configuration. SOLUTION: A component configuration information acquisition section 201 obtains component configuration information of a first explosion diagram of an object generated from a three-dimensional model of the object. A component configuration change information acquisition section 202 obtains component configuration change information indicating contents of change of the component configuration in the three-dimensional model. An identification section 203 identifies a component (unidentified component) related to the change of the component configuration from a plurality components included in a post-change three-dimensional model of the component configuration. A decision section 204 decides an arrangement position in an explosion diagram of an unidentified component identified by the identification section 203 on the basis of the component configuration information obtained by the component configuration information acquisition section 201 and the component configuration change information obtained by the component configuration change information acquisition section 202. A production section 205 produces a second explosion diagram of the object by arranging the unidentified component identified by the identification section 203 in an arrangement position decided by the decision section 204. COPYRIGHT: (C)2010,JPO&INPIT